Does macroeconomic stability matter for non-performing loans? The case of European Union countries. - Ostrowska, Aleksandra (Ekonomia i Prawo. Economics and Law, 2025)
Motivation: The quality of a loan portfolio is a key determinant of banks’ credit risk, profitability, and financial stability. It is influenced by both internal and external factors, with macroeconomic stability playing a crucial role. Macroeconomic stability affects both the demand for loans and the banks’ ability to supply credit. Growing research interest in this area stems from the recurrence of economic crises and the importance of understanding these dynamics for economic policymakers, banking sector supervisors, bank managers, and borrowers. Aim: This article aims to identify and assess the impact of selected macroeconomic stability indicators on non-performing loans (NPLs) in EU countries during the period 2014–2023, using panel data models. Results: The results of the study showed that one-year lagged NPL values, economic growth, and the unemployment rate had a significant impact on NPL levels. GDP per capita exhibited a statistically significant negative effect, indicating that its growth is associated with an increase in NPLs. In contrast, the lagged NPL values and the unemployment rate had a significant positive effect, suggesting that increases in these variables are associated with a decrease in NPLs. The inflation rate, public debt, and current account balance were found to be statistically insignificant. These relationships were consistent across both the pre-crisis period (2014–2019) and the crisis period (2020–2023). Based on these findings, recommendations were formulated for monetary and fiscal policy, as well as for the supervision of the banking sector.